Polyphenol composition of lettuce cultivars affected by mineral and bio-organic fertilisation - Dimitar Bojilov; Soleya Dagnon; Kostadin Kostadinov; Stoyan Filipov (Czech Journal of Food Sciences, 2020)
Three types of Lactuca sativa L. plants (green lettuces Batavia cv. Maritima and cv. Winter Butterhead, red lettuce Lolo rosa cv. Tuska) were investigated for their polyphenol composition. The lettuce plants were grown in polyethylene greenhouses and treated with different fertilisers. The qualitative and quantitative polyphenol composition was evaluated according to the use of mineral, organic (Italpollina and Arkobaleno) and bio (Lombricompost and EKOprop NX) fertilisers. The individual polyphenol components (caffeoyl derivatives and quercetin glycosides) were determined by high-performance liquid chromatography and the sample differences were estimated. The differences in the polyphenol content in the green lettuce cultivars in dependence on fertilisation were much higher than those in the red cultivar. In general, the red lettuce Lolo rosa cv. Tuska was characterised by the highest content of polyphenols. The highest content of all components was determined in the samples of red lettuce with the use of organic fertiliser Arkobaleno. In. the red lettuce and the green lettuce cv. Winter Butterhead organic fertilisation resulted in the higher content of polyphenols in comparison with mineral fertilisation and unfertilised samples. An exception was observed in cv. Maritima, where the unfertilised samples showed higher content of polyphenols compared to the fertilised samples